Inflation and the evolution of firm-level liquid assets - Curtis, Chadwick C.; Garín, Julio; Saif Mehkari, M. (Journal of Banking & Finance, 2017)
This paper shows that inflation has been an important determinant of firm-level liquid asset holdings. Liquid assets as a share of total assets – the cash ratio – for U.S. corporations steadily declined from the 1960s to the early 1980s, and has since steadily increased. Our empirical analysis finds that inflation is a key factor accounting for these changes. We show that these liquid asset holdings are imperfectly hedged against inflation. Hence, changes in inflation alter the real value of a firm’s liquid asset portfolio causing them to readjust these balances.